A review on intention towards consumption behavior of gastronomy in Sarawak, Malaysia - Gusti Asmadi, Utin Roziana; Samdin, Zaiton; Ab Karim, Shahrim (Universitas Pendidikan Indonesia (UPI), 2024)
As gastronomy tourism research continues to experience exponential growth, several review articles have explored the connection between gastronomy and tourism through various thematic and disciplinary lenses. However, what is currently lacking is a comprehensive summary that encompasses the interdisciplinary aspects of this research field. The main goal of this study was to carry out a comprehensive review from literature. Therefore, as a conceptual paper, this article uses the previous empirical data of the theory between Theory Planned Behavior (TPB) and Social Cognitive Theory (SCT) to obtain insight into the local gastronomy in Sarawak experiences through quantitative method by study review from literature. The conceptual framework comprises eight factors (i.e., knowledge, experiences, cultural awareness, food safety, gastronomy image, epistemic value, and environmental factors and willingness to pay). This study established an indepth understanding of the consumption of local gastronomy in Sarawak. Future academics working on the constantly evolving tourism industry will be better equipped to address current research concerns with greater understanding of the literature on Intention towards Consumption Behavior. This will further allow academics to have a solid literary basis for their studies.